Reliability and validity estimation of Urdu version of Children Emotion Management Scales (CEMS) in Pakistan - Baig, Khawer Bilal; Sadia, Haleema; Rauf, Umara; Abbas, Qasir; Ramzan, Zoobia; Tabassum, Urooj; Aljhani, Sumayah (Frontiers in Psychiatry, 2024)
The present study aimed to translate and validate Children’s Emotion Management Scales into Urdu, the national language of Pakistan. The current study comprised of three different phases i.e. phase-I: Cross-language validation over a sample of (N=169) school children, estimated at a 1-week interval. The results indicate a significant correlation (r=0.846-0.891) at p<0.01. In the phase-II, scale’s internal consistency reliability (r=0.808-0.904) and split-half reliability (r=0.737-0.898) were assessed (N=683) at p<0.01. Further, significant results for test-retest reliability analysis(N=168) were obtained (r= 0.736–0.917 at p<0.01), following the Confirmatory Factor Analysis (CFA) (N=1083). Exploratory Factor Analysis (EFA) was conducted on the same sample chosen for CFA. EFA resulted in the retention of original inhibition (INH), dysregulated expression (DYS), and emotional coping (EMO) factors. CFA findings suggest a good model fit. In Phase III, convergent and divergent validity were checked (N=385, 255, and 213). Convergent validity of INH and DYS subscales and divergent validity of EMO subscales was established, with SBI (r=0.217–0.609; 0.210–0.445; -0.026 – -0.553), SHS (r=0.417–0.441; 0.480–0.546; -0.338– -0.582), and suppression subscale of ERQ (r=0.430–0.480; 0.468–0.522; -0.245 – -0.369), at p<0.01. For divergent validity of INH and DYS subscales and convergent validity of EMO subscales, their scores were correlated with the SPS (r=-0.204– -0.350; -0.318 – -0.459; 0.191-0.531), RSE Scale (r=-0.226– -0.351; -0.279 – -0.352; 0.255–0.507), DTS (-0.290– -0.617; -0.369 – -0.456; 0.246–0.680), and reappraisal subscale of ERQ (r=-0.456 – -0.541; -0.329 – -0.544; 0.446–0.601) at p<0.01. It is concluded that the scale is reliable and valid with sound psychometric properties.